“Connectedness to Nature Scale”: Validity and Reliability in the French Context - Navarro, Oscar; Olivos, Pablo; Fleury-Bahi, Ghozlane (Frontiers in Psychology, 2017)
Connectedness to Nature represents the relationship of the self with the natural environment and has been operationalized using different scales. One of the most systematically studied in the Anglo-Saxon context is the Mayer and Frantz (2004) Connectedness to Nature Scale (CNS). In an attempt to study the psychometric properties of this instrument in a French-speaking context, three studies (Study 1 n = 204, Study 2 n = 153 and Study 3 n = 322) were carried out in France to provide evidence of the internal consistency of the CNS, as well as its convergent, discriminant and predictive validity. Moreover, as anticipated, positive correlations between the CNS and the Environmental Identity (Clayton, 2003) and environmental concerns (Amérigo et al., 2012) scales were observed. Based on factorial analyses of maximum likelihood and reliability, an improvement in the psychometric properties was identified by eliminating three items. Through confirmatory factor analysis, the factorial structure and the psychometric properties of the CNS French version were confirmed